2010
DOI: 10.1155/2010/621046
|View full text |Cite
|
Sign up to set email alerts
|

Adult Onset Still's Disease and Rocky Mountain Spotted Fever

Abstract: Adult Still's Disease was first described in 1971 by Bywaters in fourteen adult female patients who presented with symptoms indistinguishable from that of classic childhood Still's Disease (Bywaters, 1971). George Still in 1896 first recognized this triad of quotidian (daily) fevers, evanescent rash, and arthritis in children with what later became known as juvenile inflammatory arthritis (Still, 1990). Adult Onset Still's Disease (AOSD) is an inflammatory condition of unknown etiology characterized by an evan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Numerous infectious agents have been proposed as potential inciting factors for AOSD so far, but not Bartonella. [18][19][20] This is the first report suggesting the possibility that B. henselae may in part be responsible for the development of AOSD by means of either a direct inflammatory process or 'molecular mimicry' that triggers the host's autoimmune response. Further research is necessary to determine the role of Bartonella in the pathogenesis of AOSD.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous infectious agents have been proposed as potential inciting factors for AOSD so far, but not Bartonella. [18][19][20] This is the first report suggesting the possibility that B. henselae may in part be responsible for the development of AOSD by means of either a direct inflammatory process or 'molecular mimicry' that triggers the host's autoimmune response. Further research is necessary to determine the role of Bartonella in the pathogenesis of AOSD.…”
Section: Discussionmentioning
confidence: 86%
“…6 One case review also reported AOSD with Rocky Mountain spotted fever. 7 AOSD can be divided into two distinctive phenotypes, i.e., a systemic pattern and articular pattern based on cytokine profile, clinical features, and laboratory investigation. 8 Mechanisms for autoimmunity, such as activation of macrophage, inflammatory cytokines (e.g., IL-1, IL-6, IL-18, IFNδ, and TNFα), and genetic factors, along with infection play a role in the pathogenesis of AOSD as indicated in literature.…”
Section: Authorsmentioning
confidence: 99%